2005
DOI: 10.1071/sr04182
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-violet, visible, near-infrared, and mid-infrared diffuse reflectance spectroscopic techniques to predict several soil properties

Abstract: Reflectance spectroscopy techniques in the ultraviolet, visible, near-infrared and mid-infrared regions are alternatives for many traditional laboratory methods for measuring soil properties. However, debate exists over whether the near-infrared (700–2500 nm) or the mid-infrared (MIR, 2500–25000 nm) region of the electromagnetic spectrum is more useful for predicting soil properties. Therefore, the aim of this study was to compare UV-VIS-NIR and MIR spectroscopic techniques to predict several soil properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 21 publications
8
62
1
6
Order By: Relevance
“…The modeling performance for clay and sand in our study are in agreement with the results found by [32,[39][40][41] which ranged from 0.51 to 0.86 (R 2 ) and 31 to 120 g·kg −1 (RMSE) for both soil fractions. However, all these studies used different soils, methodologies, prediction algorithms and soil properties were not back-transformed in some situations.…”
Section: Predictions Of Soil Physical Propertiessupporting
confidence: 81%
See 1 more Smart Citation
“…The modeling performance for clay and sand in our study are in agreement with the results found by [32,[39][40][41] which ranged from 0.51 to 0.86 (R 2 ) and 31 to 120 g·kg −1 (RMSE) for both soil fractions. However, all these studies used different soils, methodologies, prediction algorithms and soil properties were not back-transformed in some situations.…”
Section: Predictions Of Soil Physical Propertiessupporting
confidence: 81%
“…Greater predictive performance for particle size is usually observed in the MIR compared to the VIS-NIR region. It can be explained by the stronger interaction between mid-infrared reflection spectra and soil particles by fundamental vibration processes when compared to the VIS-NIR [27,39,40].…”
Section: Predictions Of Soil Physical Propertiesmentioning
confidence: 99%
“…Three categories, based on RPD in the ranges >2, 1.4-2.0, and <1.4, were used to indicate decreasing reliability of predicting (Chang, et al, 2001). Similar results of suitable limits for RPD were also described by Dunn, et al (2002) and Pirie, et al (2005). Strong correlations were found between FTIR spectra and soil parameters: C/N ratio, C and N content, lignin, HA, soil organic carbon (SOC), inorganic carbon, metals, pH, and others.…”
Section: Chemometric Analysissupporting
confidence: 50%
“…MIR spectroscopy has frequently been applied to investigate soil properties and soil organic matter (SOM) characteristics (Aguiar, et al, 2013;Bellon-Maurel and McBratney, 2011;Calderon, et al, 2011aCalderon, et al, , 2011bDemyan, et al, 2012;Du and Zhou, 2009;Francioso, et al, 2009;Haberhauer and Gerzabek, 1999;Kaiser, et al, 2011). Currently, the combination of multivariate statistical methods used for the Fourier Transform IR (FTIR) spectra analysis has provided a powerful method for the discrimination and identification and/or quantification of single components in soils (Aguiar, et al, 2013;Bellon-Maurel and McBratney, 2011;Bornemann, et al, 2010;Calderon, et al, 2011aCalderon, et al, , 2011bD'Acqui, et al, 2010;Fernandez-Getino, et al, 2013;Janik, et al, 2007aJanik, et al, , 2007bLudwig, et al, 2008;Minasny, et al, 2008;Pirie, et al, 2005;Reeves III, 2010;Stumpe, et al, 2011;Tatzber, et al, 2010;Viscarra Rossel, et al, 2006;Yang, et al, 2012). The representation of MIR spectra is not uniform in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…literature, sodium (Na ex ) and potassium (K ex ) are among the most difficult properties to be measured with the NIR spectroscopy (Malley et al, 1999;Chang et al, 2001;Zornoza et al, 2008;Pirie et al, 2005;Dunn et al, 2002;Shepherd & Walsh, 2002;Islam et al, 2003;Volkan et al, 2010;. For the same soil property, laboratory vis-NIR methods achieved higher accuracy as compared to measurement under field soil conditions, particularly with on-line vis-NIR sensors Kuang et al, 2012).…”
mentioning
confidence: 99%